Editor's Choice – A Study of the Cost-effectiveness of Fenestrated/branched EVAR Compared with Open Surgery for Patients with Complex Aortic Aneurysms at 2 Years. (July 2018) - Michel, Morgane; Becquemin, Jean-Pierre; Marzelle, Jean; Quelen, Céline; Durand-Zaleski, Isabelle; ,
Abstract : Objectives: The aim was to assess the cost-effectiveness of fenestrated and branched stent grafts (f/b EVAR) compared with open surgical repair (OSR) in thoraco-abdominal or complex abdominal aortic aneurysms (TAAA/AAA) at 2 years. Methods: Two matched cohorts of patients with TAAA or complex AAA were compared after a follow-up of two years. Patients included in the WINDOW French multicentre prospective registry were treated by f/b EVAR, and OSR patients were extracted from the French national hospital discharge database. All cause mortality was assessed along with readmissions and hospital costs. The association between treatment and 2 year mortality was assessed by uni/multivariate Cox regression analyses using pre- and post-operative characteristics. Incremental cost-effectiveness ratios (ICER) were estimated for para/juxtarenal AAA, and infra- and supra-diaphragmatic TAAA. Results: A total of 268 high risk patients were treated by f/b EVAR and 1678 average or low risk patients were treated with OSR during the same period. Mortality did not significantly differ between the groups (14.9% vs. 11.8%, p  = .150) and multivariate Cox regressions did not find an association between 2 year mortality and treatment. Similar proportions of patients were readmitted at least once (69.7% with f/b EVAR vs. 64.2% with OSR, p  = .096) but f/b EVAR patients had more readmissions on average (2.2 vs. 1.7, p  = .001). Two year hospital costs were higher in the f/b EVAR group (€46, 039 vs. €22, 779, p  < .001). At 2 years, f/b EVAR was dominated (more expensive and less effective), except in the supra-diaphragmatic TAAA subgroup with an ICER of €42, 195, 800 per death averted. Conclusions: f/b EVAR in high risk patients offers similar 2 year mortality to OSR performed in lower risk patients but at a higher cost. The cost is mainly driven by the cost of the stent graft, which is not compensated for by lower healthcare resource consumption. Further studies are necessary to evaluate the cost-effectiveness in low risk f/b EVAR patients who may experience fewer complications.